Penguatan Pendidikan Karakter (PPK) Siswa SMAN 1 Kampar Timur Melalui Pelatihan Tari Zapin Pecah Dua Belas - Evadila Evadila; Nurmalinda Nurmalinda; Laila Fitriah (Lamahu: Jurnal Pengabdian Masyarakat Terintegrasi, 2025)
The declining interest of SMAN 1 Kampar Timur students in traditional Malay Riau dance has contributed to a weakening of character development. The absence of structured training programs in traditional dance has also resulted in limited effective engagement with local cultural heritage. A training program focused on Zapin Pecah Dua Belas dance was implemented to address these issues. This initiative aimed to strengthen students’ character, channel their artistic interests and talents, and rekindle appreciation for traditional Malay Riau dance, particularly Zapin Pecah Dua Belas dance. The program comprised four phases: preparation, implementation, presentation, and evaluation, and was conducted over one day. The training led to measurable character enhancement, namely, cooperation, discipline, self-confidence, creativity, courtesy, communication, sociability, and perseverance, through the mastery of six core movement patterns in Zapin Pecah Dua Belas dance. Moreover, the program successfully facilitated students’ engagement with traditional dance and fostered a renewed cultural pride. The ethnopedagogical training program through Zapin Pecah Dua Belas Dance received a positive response from the partner institution and is recommended for continuous integration by school teachers into cultural arts education.